2019
DOI: 10.4081/ija.2019.1297
|View full text |Cite
|
Sign up to set email alerts
|

Chia (Salvia hispanica L.) as a novel forage and feed source: A review

Abstract: Chia (Salvia hispanica L.), is a traditional pre-Colombian food crop from Central America. Being considered the richest botanical source of omega-3 fatty acids, it has recently been rediscovered as a functional food and feed. A growing body of literature indicates that dietary chia seeds greatly improve animal products quality without compromising growth, productivity and organoleptic quality. Chia is mainly cultivated as a seed crop but recently interest has been raised on biomass production as a potential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 109 publications
(176 reference statements)
1
12
0
1
Order By: Relevance
“…A maximum of above 60% ALA is the main FA, followed by linoleic acid. The percentage of ALA we found is in line with values reported in the literature as reviewed in Reference [9] and slightly lower than the values reported in Reference [29]. The omega-3 content of chia vegetative parts is remarkable compared to the average values reported for some common forage grasses and legumes [70] and higher than values reported for other omega-3-rich species such as birdsfoot trefoil (Lotus corniculatus L.) and salad burnet (Sanguisorba minor Scop.)…”
Section: Forage Qualitysupporting
confidence: 89%
See 1 more Smart Citation
“…A maximum of above 60% ALA is the main FA, followed by linoleic acid. The percentage of ALA we found is in line with values reported in the literature as reviewed in Reference [9] and slightly lower than the values reported in Reference [29]. The omega-3 content of chia vegetative parts is remarkable compared to the average values reported for some common forage grasses and legumes [70] and higher than values reported for other omega-3-rich species such as birdsfoot trefoil (Lotus corniculatus L.) and salad burnet (Sanguisorba minor Scop.)…”
Section: Forage Qualitysupporting
confidence: 89%
“…Literature on the effects of agronomic practices on chia biomass production is quite scarce [29], especially regarding the effect of sowing density and fertilization [27,37]. This is partially due to the fact that chia is mainly grown as a seed crop, and only recently has interest in fodder production been raised [4,9,25]. The chia shoot biomass values found in our experiment are higher than the values obtained in northwestern Argentina [34] across different locations and seeding dates (between 0.49 and 4.67 t ha −1 ) and as affected by geographic location [35] (between 1.12 and 4.18 t ha −1 ).…”
Section: Crop Growth and Forage Yieldmentioning
confidence: 99%
“…Whole plant biomass yield of Chia has been reported to vary from 492 to 3675 kg ha -1 from northwestern Argentina, Ghana, Greece, northern Chile, and southern Italy. Jamshidi et al (2019) observed lack of published works on the use of Chia herbage in animal nutrition, however forage use of Chia vegetative parts was suggested by Peiretti and Gai (2009), who determined a whole panel of chemical analyses relevant for animal nutrition.…”
Section: Resultsmentioning
confidence: 99%
“…The cultivation of chia has recently expanded to nations around the world because the plant seeds are rich in dietary nutrients (fiber, antioxidants, minerals and vitamins, proteins, and unsaturated fatty acids) and phenolic compounds often associated with health benefits [ 2 ]. Apart from the nutritional value of the seeds, chia leaves and stems are a good source of polyunsaturated fatty acids (PUFA) and other essential oils, which are used as feed additives in ruminant nutrition [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%